(untitled) (International Journal of Geoscience, Engineering and Technology, 2022)
The disorderly growth associated with population density has been the main factor causing the increase in areas of environmental and geological risk in recent years. The objective of this study is to identify and classify the main risk areas in the Buritis and Castro Pires neighborhoods located in Teófilo Otoni – MG/Brazil. Initially, a field survey was carried out to identify the main areas of risk. For the evaluation of the areas, the Mapping of Risks on Slopes and Margins manual was used, prepared by the Ministry of Cities, which classifies the risk factors in R1, R2, R3 and R4 into low, medium, high and very high risk, respectively. Six risk areas were identified: areas 1, 2 and 5, located on Ewald Middeldorf street, were classified as risk level R4; areas 3 and 4 on Sebastião Gomes de Matos Street with risk level R3; and area 6 on 8 de Janeiro Street with risk level R2.